THE AERODYNAMICS ANALYSIS OF AIRFOILS FOR HORIZONTAL AXIS WIND TURBINE BLADE USING COMPUTATIONAL FLUID DYNAMIC - Mokhetar, Abdulhafiz Younis; Yohana, Eflita; Suryo Utomo, MSK. Tony (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2014)
This paper included in designing and simulating for 2D. It may use two software's called Gambit and FLUENT to generate the data from the fluid flow cases. In this research select two models NACA airfoil NACA4412 and NACA4415. Chose NACA 4412 because lift coefficient is higher than NACA4415. In this study computational flow over an airfoil at different angles of attack (0º, 5º,10º,15º ,20º) using CFD (Computational fluid dynamics) simulation two dimensional airfoil NACA 4412 and NACA4415 CFD models are presented using ANSYS-FLUENT software. For this model Using turbulent viscosity k-epsilon (standard wall function) near the wall and wind velocity 5 m/s Here, NACA 4412 airfoil profile is considered for analysis of wind turbine blade. Geometry of airfoil is created using GAMBIT 2.4.6 and CFD analysis is carried out using FLUENT 6.3.26 at various angles of attack from 0º to 20º. Lift and Drag forces along with the angle of attack are the important parameters in a wind turbine system. The Lift and Drag forces are calculated at different sections for angle of attack from 0o to 20o for low Reynolds number. The analysis showed that the angle of attack of 10o has high Lift/Drag ratio. The airfoil NACA 4412 is analyzed based on computational fluid dynamics to identify its suitability for its application and good agreement is made between the results